Pengaruh Literasi Keuangan Terhadap Minat Menabung di Bank Syariah (BSI) - Lucyana Widiawati; Imamah Hastiati Hajidah; Rani Ambar wati; Henny Saraswati; Wahyu Hidayat (Student Research Journal, 2023)
This study aims to analyze the effect of Islamic financial literacy on the intention to save in Islamic banks (BSI). This study uses a quantitative method with a questionnaire as a research instrument. The population in this study were undergraduate students and 31 respondentsl were takenl as samplesl using the quotal sampling technique. Thel data analysisl technique usedl is simplel linear lregression. So that the resultsl obtained in the study showed that Islamic financial literacy had a positive and significant effect on the intention to save in Islamic banks (BSI) with a significance value of 0.000 <0.005 with the regression equation Y = 0.616 + 0.857X + e . Basedl on thel results ofl research by Indonesian Islamicl banks (BSI), it emphasizes financial literacy of Islamicl banks andl their productsl so thatl they canl reach Indonesianl people, especiallyl students.